The Effect Of Digital Literacy And E-Commerce Toward Digital Entrepreneurial Intention - Maulani, Galih Abdul Fatah; Fauziah, Nida; Mubarok, Teten Mohamad Sapril (Entrepreneurship Faculty, Universitas Garut, 2023)
This research examines the impact of digital literacy and e-commerce experience on student’s digital entrepreneurship intention. Digital literacy is important in the digital technology era, and e-commerce experience also shapes the view of the digital business world. This study explores the relationship between digital literacy, e-commerce experience, and student’s digital entrepreneurship intention. Through this study, it is expected that the important factors influencing digital entrepreneurship intention among students will be revealed, as well as the importance of digital understanding in today’s business. The population in this study are students at Garut University. This type of research is quantitative research with a non-experimental / survey research type. The sample used in this study was 359 respondents, distributed to respondents using a questionnaire directly and through Google form media, then processed using SPSS statistics 26 using a simple purposive sampling technique. The results of the study state that the Digital Literacy Variable has a positive and significant effect of 46.7% on Digital Entrepreneurship Interest. The E-commerce Variable has a positive and significant effect of 40.8% on Digital Entrepreneurship Interest. The Digital Literacy and E-commerce Variables have a positive and significant effect of 49.1% on Digital Entrepreneurship Interest. While the remaining 50.9% is influenced by other variables not mentioned in this research model